The tests of the belonging of functions to the classes Fn(D) and Qn(D) - Kirjatskis, Jevgenijus; Kirjackis, Eduardas (Lietuvos matematikos rinkinys, 2021)
In the work with the aid of the divided and finite differences are introduced classes Fn(D) and Qn(D) of functions holomorphic in region D. Different properties of functions from these classes are studied, the tests of the belonging of functions to the mentioned classes are established.